Transfer of muscle strength between single-joint and multi-joint exercises for lower limbs - Hammerová, Tereza; Chlápek, Jan; Králová, Tereza; Vodička, Tomáš; Kováčiková, Zuzana; Ondráček, Jan (Studia Sportiva, 2020)
Most strength and conditioning coaches deal with the question in the training plan, how to supplement specific exercises, or which non-specific exercises would be the most suitable for achieving the set purpose. This study aims to assess what strength transfer with a focus on the lower limbs is projected from the selected strength intervention program (the right leg exercises only single-joint exercises: leg extension on machine and leg curl; the left leg exercises only multi-joint exercises: deadlift and leg press) to the force of the knee joint flexors and extensors during the eccentric and the concentric contraction. In one training session, the participants repeated every exercise five times in four series. The load intensity was around 90% of 1RM and was increased by 5% after the first and the fifth week. The rest interval was always three minutes long. For the left lower limb, the highest transfer (0.20) was from the leg press to the knee joint extensor at the eccentric contraction and from the deadlift was the highest transfer (0.19) to the knee joint extensor at the eccentric contraction. For the right lower limb, the highest transfer (0.53) was from the leg extension on a machine to the knee joint flexor at the concentric contraction and from the lying leg curl was the highest transfer (0.47) to the knee joint flexor at the concentric contraction.
Keywords: kosterní svaly; Lower Extremity; Leg; dolní končetina; Exercise Movement Techniques; cvičení; lidé; Humans; techniky cvičení a pohybu; Exercise; Muscle, Skeletal; bérec